(G'/G)-expansion method and its applications to the 2-dimensional burgers equation and coupled burgers type equation - Inan, Ibrahim E.; Kiliç, Bülent; Duran, Serbay (My University, 2011)
In this paper, we implemented the (G'/G) - expansion method for the traveling wave solutions of the 2-dimensional Burgers equation and coupled Burgers type equation. By using this scheme, we found some traveling wave solutions of the above-mentioned equations. © IDOSI Publications, 2011.
Keywords: (G'/G) - expansion method; 2-dimensional burgers equation; Coupled burgers type equation; Traveling wave solutions